2013
DOI: 10.1111/nph.12486
|View full text |Cite
|
Sign up to set email alerts
|

Early transcriptional responses to mercury: a role for ethylene in mercury‐induced stress

Abstract: SummaryUnderstanding the cellular mechanisms of plant tolerance to mercury (Hg) is important for developing phytoremediation strategies of Hg-contaminated soils. The early responses of alfalfa (Medicago sativa) seedlings to Hg were studied using transcriptomics analysis.A Medicago truncatula microarray was hybridized with high-quality root RNA from M. sativa treated with 3 lM Hg for 3, 6 and 24 h. The transcriptional pattern data were complementary to the measurements of root growth inhibition, lipid peroxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 85 publications
9
72
0
Order By: Relevance
“…The molecular mechanism of how plants can cope with different HM stresses varies from plant to plant, but in general, ethylene and its cross talk with other phytohormones or with signaling molecules are important for plant adaptation to HM-induced oxidative stress (Thapa et al, 2012;Montero-Palmero et al, 2014a, 2014b. It has been found that not only the production of ethylene but other phytohormones are also affected by excessive HM.…”
Section: Ethylene and Its Cross Talk With Other Hormones And Signalinmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular mechanism of how plants can cope with different HM stresses varies from plant to plant, but in general, ethylene and its cross talk with other phytohormones or with signaling molecules are important for plant adaptation to HM-induced oxidative stress (Thapa et al, 2012;Montero-Palmero et al, 2014a, 2014b. It has been found that not only the production of ethylene but other phytohormones are also affected by excessive HM.…”
Section: Ethylene and Its Cross Talk With Other Hormones And Signalinmentioning
confidence: 99%
“…Other studies also suggested that an appropriate control of ethylene signaling could be used as a biotechnological approach to improve HM stress tolerance. In Arabidopsis, EIN2 gene function was found to be required for plant Al and Hg sensitivities, as root growth inhibition under HM stress was alleviated in all the Arabidopsis ein2-1, ein2-5, and etr1-3 single mutants (Sun et al, 2010;Montero-Palmero et al, 2014a). By contrast, the EIN2 gene was reported to be important for Pb resistance in Arabidopsis plants , suggesting that the role of ethylene in plant responses to HM stress is complex and, perhaps, depends on the types of HMs to which the plants are exposed.…”
Section: Improvement Of Plant Tolerance To Hm: An Approach Of Modifyimentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that exposure to HMs enhances the production of ET [59] due to increased 1-aminocyclopropane-1-carboxylic acid (ACC) synthase (ACS) activity in metal stressed plants [60]. Cross talk between ET and stress signaling molecules like NO is important to understand the mechanisms of plant adaptation to HM-induced oxidative stress [61][62][63]. More recently, Thao et al [51] suggested a possible link between NO and ET through MAPKs in plants exposed to HM stress.…”
Section: No-phytohormone Cross Talk Under Heavy Metals Stressmentioning
confidence: 99%
“…However, up to now, little is known about the adverse effects of Hg on the cellular structure of lupin leaves and nodules or on their function. These studies are necessary for better understanding of the cellular mechanisms of plant tolerance to Hg, which is important for developing phytoremediation strategies of Hg-contaminated soils and environments (Montero-Palomero et al 2014).…”
Section: Introductionmentioning
confidence: 99%